Penerapan Bimbingan Kelompok terhadap Kepercayaan Diri Remaja di Desa Timbang Lawan, Bahorok - Nurussakinah Daulay; Siti Rahmadanti Siregar; Siti Hamidah; Nurmiah Hasibuan; Febri Dwi Widodo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to see how the application of group guidance to adolescent self-confidence in Timbang Lawan village, Bahorok Langkat. In the implementation of this research, it was applied to 8 teenagers with an age range of 12-15 years. Data obtained from observations and interviews. The results of observations and interviews were analyzed using descriptive analysis techniques. Based on the results of research and discussion, it is known that there is a problem of low self-confidence in adolescents in the village due to not optimal potential abilities in solving problems or their formal conditions, such as: lack of ability in competition, and intelligence. Based on this, group guidance services were applied so that the results obtained that group guidance services had a positive effect on adolescents in Timbang Lawan Village, Bahorok. Keywords : Guidance Group, Confidence, teenager